Interactional Scaffolding in EFL Reading Classrooms: A Classroom-Based Study of Cooperative Learning Practices - Karim, Lelan; Abid, Abid; Kau, Magvirah El Walidayni (Jambura Journal of English Teaching and Literature, 2025)
This qualitative study examines how cooperative learning is implemented by an EFL teacher to support students’ reading comprehension in a lower-secondary context at a school in Indonesia. Drawing on four classroom observations and a semi-structured teacher interview, the study investigates how cooperative learning functions as an interactional scaffold during reading instruction. Data were analyzed thematically using an interactive analytical approach. The findings reveal three interrelated ways in which cooperative learning fostered reading comprehension: (1) structuring peer-mediated reading through cooperative routines, (2) scaffolding comprehension through teacher-guided interaction, and (3) sustaining engagement through recognition and affective support. Cooperative learning was enacted through Jigsaw and Think-Pair-Share, which created structured opportunities for peer explanation, shared responsibility, and negotiation of meaning. Although students initially experienced confusion and hesitation, engagement increased as instructional routines stabilized and teacher mediation became more explicit. Instead of demonstrating causal learning gains, this study offers process-level, classroom-based insights into how cooperative learning supports EFL reading comprehension through interaction and pedagogical practices.